A rare primary pulmonary tumor of childhood - Kotiloğlu, Esin; Kaya, Handan; Kıyan, Gürsu; Tüney, Davut; Canpolat, Cengiz (The Turkish Journal of Pediatrics, 2002)
Pleuropulmonary blastoma (PPB) is known to be the pulmonary blastoma of childhood. It has a range of macroscopic and microscopic features which appear to correlate with eventual prognosis. Type 1, presenting as a multicystic lesion, occurs at an earlier age and has a more favorable prognosis than other types. The presented case of type 1 PPB had a microscopic focus of rhabdomyosarcoma. Although this patient was disease-free one year after the initial diagnosis without chemotherapy, he presented at 14 months with local dissemination and cardiac metastasis, revealing the inevitable chemo-radiotherapy need in PPB.